2014
DOI: 10.1002/2014gl060070
|View full text |Cite
|
Sign up to set email alerts
|

Seismic imaging of a fluid storage in the actively extending Apennine mountain belt, southern Italy

Abstract: A picture of the upper crustal structure of the Irpinia active faults system in southern Italy was obtained by combining new geological evidences, lithological properties, and microseismicity distribution. P and S wave velocity models indicate high V P /V S and low V P × V S values, suggesting fluid accumulation within ã 15 km wide rock volume where intense microseismicity is located. The 1980 Irpinia, M s 6.9, earthquake nucleated within the same fault-bounded volume. We suggest that concentration of backgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
90
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(108 citation statements)
references
References 49 publications
14
90
4
Order By: Relevance
“…The strong lateral SW-NE variation of Q s coincides with the NW-SE trending lateral velocity discontinuity previously revealed by Amato et al [1992] and recently confirmed by Amoroso et al [2014] and Improta et al [2014], affecting the shallow upper crustal volume across the Irpinia earthquake fault zone. This discontinuity can be associated with the contrast between the thick cover of low-velocity, high-attenuation Miocene basin sediments to the NE and the high-velocity, low-attenuation carbonate outcrops of the Apennine platform to the SW [Ascione et al, 2013].…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The strong lateral SW-NE variation of Q s coincides with the NW-SE trending lateral velocity discontinuity previously revealed by Amato et al [1992] and recently confirmed by Amoroso et al [2014] and Improta et al [2014], affecting the shallow upper crustal volume across the Irpinia earthquake fault zone. This discontinuity can be associated with the contrast between the thick cover of low-velocity, high-attenuation Miocene basin sediments to the NE and the high-velocity, low-attenuation carbonate outcrops of the Apennine platform to the SW [Ascione et al, 2013].…”
Section: Discussionsupporting
confidence: 83%
“…We selected the best located events in the 3-D velocity model of Amoroso et al [2014] among those that occurred from August 2005 to April 2011 and were recorded by the stations operated by the University of Naples ISNet (Irpinia Seismic Network, AMRA) and INGV (Istituto Nazionale di Geofisica e Vulcanologia) ( Figure 1). We thereby analyzed a data set of 4801 t * P and 1833 t * S relative to 670 earthquakes with local magnitude 0.1 ≤ M L ≤ 3.2.…”
Section: Attenuation Tomography: Data Method and Inversion Strategymentioning
confidence: 99%
See 3 more Smart Citations